ANALISIS EVIDENCE BASED NURSING: INTERVENSI COLD COMPRESS DALAM PENURUNAN SKALA NYERI PADA PASIEN FRAKTUR TERTUTUP DI IGD RS. BHAYANGKARA TK. I R. SAID SUKANTO - Hilmi Yoda, (2023)
Bone discontinuities known as closed fractures can result from both trauma and non-trauma. One of the health issues that patients with closed fractures may suffer is severe discomfort. This KIAN was written with the intention of applying an analysis of acute pain nursing care given to patients with closed fractures using cold packs in a hospital emergency room. I. R. Said Sukanto, Bhayangkara Tk. During the evaluation phase, it was discovered that managed patients reported pain on a scale of 8 (1-10) and resumed patients on a scale of 8 (1-10). felt constantly, kind of like being stabbed. Acute pain was identified as the primary nursing diagnosis based on the findings of the evaluation that was conducted. The administration of cold compress therapy using coldpack media is one of the therapies used to manage acute pain nursing concerns. The evaluation's findings demonstrate that treating acute pain in individuals with closed fractures with cold compress treatment and coldpack media is successful. Every nurse should take into account the nursing care for patients with closed fractures who feel acute pain in order to avoid more significant health issues.